The Effect of Digital Literacy, Technological Adoption, and Collaborative Learning on Student Engagement in Business Education - Arjang, Arjang; Syahputra, M; Fahruri, Arief; Silva, Dewi (International Education Trend Issues, 2024)
This study explores the influence of digital literacy, technological adoption, and collaborative learning on student engagement in business education. Utilizing a quantitative research design, data were collected from 300 undergraduate students enrolled in business programs through a structured questionnaire. The analysis employed descriptive statistics, correlation analysis, and multiple regression techniques to investigate the relationships between the variables. The results revealed that digital literacy, technological adoption, and collaborative learning significantly contribute to student engagement, with collaborative learning emerging as the strongest predictor. The findings underscore the importance of enhancing digital literacy and promoting technology use in educational settings, alongside fostering collaborative learning experiences, to improve student engagement in business education. These insights have implications for educators and curriculum designers seeking to create more effective and engaging learning environments.